Gestión Administrativa – Financiera y su incidencia en el cumplimiento de metas de la Dirección Distrital de Salud 12D01 Babahoyo, Baba, Montalvo - Crespo Fuentes, Valentina Vanessa (2017)
In the city of Babahoyo, Province of Los Ríos, the research entitled "Administrative and Financial Management and its impact on the fulfillment of goals of the District Health Directorate 12D01 Babahoyo, Baba, Montalvo" was carried out, whose main objective is to analyze the incidence of the administrative - financial management in the achievement of goals. The specific objectives were aimed at analyzing the relationship of the administrative - financial management with the fulfillment of goals of the District Health Directorate 12D01, evaluating the extent to which the administrative - financial management integrated to the institutional values ​​contributes and elevates the fulfillment of goals , and implement strategies that allow the administrative-financial management of the District 12D01 Health Directorate to improve compliance with the goals established in the institutional planning. The research methodology to be implemented was descriptive, developed in the administrative and financial area of ​​the District Health Directorate and the operating units, applying interviews and surveys to a population of 36 people. In relation to the results obtained in the investigation, it was determined that there are problems in the 12D01 District Health Department since they do not fully comply with the goals established in terms of institutional planning, the institutions lack strategies that allow compliance with the goals through the administrative and financial management developed in the institutions, since the activities carried out partially contribute to fulfillment, the District Health Office does not comply with the requirements of the dependencies due to the fact that the operational units sometimes fall behind when requesting the orders, which causes that they do not fulfill the demands of the users when not being able to satisfy their needs due to the adjusted budget that prevents the total fulfillment of the institutional goals. xi Therefore, the administrative strategies to be proposed would help the total fulfillment of the objectives and goals.